2012
DOI: 10.1096/fj.12-218081
|View full text |Cite
|
Sign up to set email alerts
|

Programmable nanoparticle functionalization forin vivotargeting

Abstract: The emerging demand for programmable functionalization of existing base nanocarriers necessitates development of an efficient approach for cargo loading that avoids nanoparticle redesign for each individual application. Herein, we demonstrate in vivo a postformulation strategy for lipidic nanocarrier functionalization with the use of a linker peptide, which rapidly and stably integrates cargos into lipidic membranes of nanocarriers after simple mixing through a self-assembling process. We exemplified this stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 55 publications
0
53
0
Order By: Relevance
“…We have previously reported that the cationic amphipathic peptide designated as "p5RHH" (VLTTGLPALISWIRRRHRRHC) is capable of siRNA transfection without significant cytotoxicity at all tested doses (8). This novel sequence lacks the toxicity profile of its full parent compound, melittin, because it features a truncation of six terminal amino acids that prevents peptide-induced cytolytic membrane pore formation at low doses in the blood stream (11)(12)(13)), yet when concentrated in endosomes still promotes endosomolysis and siRNA escape (9). The noncovalent coupling, self-assembling formulation strategy is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that the cationic amphipathic peptide designated as "p5RHH" (VLTTGLPALISWIRRRHRRHC) is capable of siRNA transfection without significant cytotoxicity at all tested doses (8). This novel sequence lacks the toxicity profile of its full parent compound, melittin, because it features a truncation of six terminal amino acids that prevents peptide-induced cytolytic membrane pore formation at low doses in the blood stream (11)(12)(13)), yet when concentrated in endosomes still promotes endosomolysis and siRNA escape (9). The noncovalent coupling, self-assembling formulation strategy is depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…jci.org Volume 124 Number 10 October 2014 p5) that serves well as a "cargo carrier" capable of inserting rapidly into lipid membranes, but is substantially less lytic compared with native melittin (5,700% decrease; ref. 38). After uptake of the nanoparticles into endosomes, the residual lytic activity of the p5 peptide enables the disruption of endosomal membrane, allowing the siRNA to escape, as previously shown (14).…”
Section: Discussionmentioning
confidence: 77%
“…We recently reported the development of an amphipathic peptide-based siRNA nanoplatform (13,14) that uses a modified version of the bee venom component melittin to transport siRNA (15). Melittin is a well-studied peptide with pore-forming features that derive from its ability to insert into lipid membranes stably through hydrophobic interactions among resident membrane phospholipids interacting with its α-helical peptide secondary structure (16,37,38). Subsequent multimeric oligomerization establishes a membrane pore, resulting in disruption and cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that no 19 F signal was detected in the descending aorta and that smaller plaques commonly occur there (26), an improved sensitivity might be needed to detect very small plaque formations. Fortunately, several avenues are available for future improvements, such as an optimized PFC administration scheme; a higher PFC load in the emulsion (safe formulations with up to 30% instead of the 10% used here have been reported [27]); the implementation of novel image reconstruction methods, such as compressed sensing (28); or the postformulation addition of a targeting ligand (29). Furthermore, the exact correlation of the 19 F MR signal with the macrophage load as can be determined through histologic examination should be established, while the exact populations that internalize PFC could be investigated by means of flow cytometry.…”
Section: Discussionmentioning
confidence: 99%